The second wave of global liquidity: Why are firms acting like financial intermediaries? - Julian Caballero; Ugo Panizza; Andrew Powell (Graduate Institute of International and Development Studies, 2015)
Recent work suggests that non-financial firms have acted like financial intermediaries particularly in emerging economies. We corroborate these findings but then ask why? Our results indicate evidence for carry-trade activities but focused in countries with higher levels of capital controls, particular controls on inflows. We find little evidence for such activities given other potential motives. We posit that this phenomenon is due more to the reaction to low global interest rates and strong capital inflows than to incomplete markets or the retreat of global banks due to impaired balance-sheets or tighter regulations.
Keywords: E51; F30; F33; 330; corporate finance; bond issuance; currency mismatches; carry-trade; capital controls